028 Birth size differences between white and Pakistani-origin infants by generation: results from the Born in Bradford Cohort Study. (16th November 2010) - West, J; Lawlor, D A; Fairley, L; Wright, J; ,
Abstract : Background: Previous studies have shown marked differences in birthweight between babies born in the UK of South Asian origin and those of UK origin. Whether such differences persist across generations in contemporary populations, the mechanisms underlying them and the extent to which other dimensions of birth size vary between these two groups is unclear. Objective: To describe differences in term birthweight, head, arm and abdominal circumference and skinfolds between Pakistani origin and white British origin infants and to investigate whether the magnitude of any differences reduces depending on whether the parents and grandparents of Pakistani infants are born in the UK or Pakistan. Design: Birth cohort study (Born in Bradford (BiB)). Setting: Bradford, UK. Participants: 1838 white British and 2222 Pakistani mothers recruited to BiB who completed a questionnaire at 26 weeks gestation and their babies born between Sept 2007 and Nov 2009. Main outcome measures: Birthweight, head, arm and abdominal circumference and skinfolds. Results: Pakistani babies were lighter (mean difference 227.6g, 95% CI 198.3 to 256.8), had smaller head, arm and abdominal circumferences (mean differences 0.43cm, 95% CI 0.30 to 0.56; 0.22cm, 95% CI 0.10 to 0.34; 1.25cm, 95% CI 1.02 to 1.39 respectively) and smaller subscapular and triceps skinfold thickness (mean differences 0.22 mm, 95% CI 0.12 to 0.32 and 0.21 mm, 95% CI 0.13 to 0.29) than white British infants. Differences remained significant following adjustment for deprivation. Mean birthweight was highest in Pakistani infants when both parents were born in Pakistan (3206 g) and was lowest when both parents were UK-born (3165g). Conclusions: These results reaffirm that significant differences in birth size exist between white British and Pakistani origin infants in the UK. Despite the assumption that differences will reduce over successive generations, mean birthweight has not increased in infants of UK-born Pakistani origin parents compared with infants of Pakistani born parents. This suggests that differences may be genetically determined or are affected by epigenetic or persisting behaviour characteristics. Further analysis will include adjustment for additional socio-economic variables, other maternal and family characteristics and birthplace of maternal and paternal grandparents.